Optimizing the Mother–Toddler Class to Address Wasting Through the Tangan Baliku Program Towards a Healthy and High-Quality Generation in the Working Area of Purbaratu Primary Health Center - Ladyvia, Fiyola; Khaerunisa, Ismah; Leandra, Maulinda Nur Amalina; Siagian, Rosmawaty Irma Suryani; Yatini, Yatini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2025)
Wasting in children under five remains a significant public health problem, especially in developing countries like Indonesia, where nutritional issues such as wasting, stunting, and underweight are still prevalent. This study aimed to develop and implement a community-based innovation program named Tangan Baliku (Integrated Management of Underweight Children) to address the high incidence of wasting in the working area of Purbaratu Primary Health Center. This innovation was designed and implemented in April 2022 through cross-sectoral collaboration, focusing on promotive, preventive, curative, and educational approaches. The methodology used was a descriptive participatory approach involving community empowerment through optimizing the existing mother–toddler class, home visits, nutrition counseling, supplementary feeding, and regular monitoring. The results show that Tangan Baliku effectively increases early detection and management of underweight children, improves mothers' knowledge of nutrition, and encourages higher participation in toddler health services. It also helps in reducing the number of children with poor nutritional status through structured follow-up and referral systems. In conclusion, the Tangan Baliku program is a comprehensive and sustainable strategy that addresses wasting by strengthening maternal involvement, community participation, and cross-sector collaboration in child nutrition improvement. This program contributes to better health outcomes for children under five and supports the development of a healthy and high-quality future generation.